POSTPARTUM MASSAGE AND SPA ENTREPRENUERSHIP: MENGANTAR MIORI MENGGAPAI MIMPI - Ira Titisari; Rahajeng Siti Nur Rahmawati; Indah Rahmaningtyas (Politeknik Kesehatan Kemenkes malang, 2021)
One of the problems that occur during the puerperium is postpartum depression. One way to prevent postpartum depression is by giving postnatal massage. Massage after childbirth, can relieve pain, help postpartum mothers to be more relaxed, support breastfeeding efforts, relax muscles, increase circulation and reduce stress hormones, bring relaxation and relieve stress. The benefits of postpartum massage are so great, then this is a very good business opportunity that can be done by alumni who want and are starting a business that does not come out of midwifery itself. The purpose of this community service is to create new entrepreneurs based on science and technology. The community service method is carried out by inviting alumni who want and are starting a business to take part in post partum message and spa training. Before the training, a pre-test was carried out and after the training was a post-test, practicum assignments were made with videos and made a post-partum message and spa entrepreneurship business plan. The results of community service from the pre-test showed that 50% of the knowledge was good, for the post-test 100% of the knowledge was good, 100% of the post-partum message and spa practicum video assignments were collected and 100% of the participants had made a post-partum message and spa entrepreneurship business plan.